2022
DOI: 10.3390/nu14245351
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Chain Fatty Acids and Breast Cancer Risk by Receptor and Pathological Subtypes

Abstract: Introduction: Medium-chain fatty acids contain 6–12 carbon atoms and are absorbed directly into the blood vessels, proceeding to the portal vein and, finally, to the liver, where they are immediately utilized for energy. We aimed to determine the medium-chain fatty acid levels in women with and without breast cancer. Materials and Methods: A total of 200 women (100 breast cancer subjects and 100 control subjects) were recruited for the study as per the inclusion and exclusion criteria. Blood samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…Consistent with our results, a case-control study examined plasma levels of medium-chain SFAs and observed that lower levels of caprylic acid (C8:0) and lauric acid (C12:0) might be associated with higher odds of breast cancer. 28 Furthermore, our results were in concordance with previous experimental studies on molecular mechanisms. In vivo studies on breast cancer cells demonstrated that medium-chain SFAs exert anticancer effects on human breast cancer cells by down-regulating cell cycle regulatory genes, and up-regulating genes related to apoptosis.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with our results, a case-control study examined plasma levels of medium-chain SFAs and observed that lower levels of caprylic acid (C8:0) and lauric acid (C12:0) might be associated with higher odds of breast cancer. 28 Furthermore, our results were in concordance with previous experimental studies on molecular mechanisms. In vivo studies on breast cancer cells demonstrated that medium-chain SFAs exert anticancer effects on human breast cancer cells by down-regulating cell cycle regulatory genes, and up-regulating genes related to apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…Food & Function cancer. 28 Furthermore, our results were in concordance with previous experimental studies on molecular mechanisms. In vivo studies on breast cancer cells demonstrated that mediumchain SFAs exert anticancer effects on human breast cancer cells by down-regulating cell cycle regulatory genes, and upregulating genes related to apoptosis.…”
Section: Papersupporting
confidence: 92%
See 3 more Smart Citations